Attitudes of Healthcare Professionals and General Population Toward Vaccines and the Intention to Be Vaccinated Against COVID-19 in Spain - Iguacel, Isabel; Luna Maldonado, Aurelio; Luna Ruiz-Cabello, Aurelio; Samatán, Eva; Alarcón, Judith; Ángeles Orte, María; Santodomingo Mateos, Silvia; Martínez-Jarreta, Begoña (Frontiers in Public Health, 2021)
Background: To achieve herd immunity, the acceptance of the COVID-19 vaccine by population, especially healthcare professionals, plays a key role. The objective of the present paper is to address differences in attitudes among Spanish healthcare professionals compared to general population regarding COVID-19 vaccination. Methods: This cross-sectional study included data on 2,136 adults (n=664 healthcare professionals) from an online survey conducted from May 6th to June 9th, 2021. The Vaccination Attitudes Examination (VAX) Scale was used to measure the negative attitudes towards vaccines. Four sub-scales were calculated: mistrust of vaccine benefit, worries about unforeseen future effect; Concerns about Commercial Profiteering and Preference for Natural Immunity. Generalized Lineal Mixed Models were conducted to study these associations. Results: Between 10.2% and 22.6% of the subjects showed high levels of negative attitudes towards vaccines. However, only 1.5% of our sample (2.1% among healthcare professionals) refused to get the vaccine of COVID-19 when it was offered because they chose otherwise. Retired people showed the lowest concerns and the highest trust in vaccines. No statistically significant effects were found between working in a healthcare field and having higher positive attitudes towards vaccines. Conclusion: Low levels of rejection against COVID-19 vaccine were identified in the present sample. However, despite being at a higher risk, heath care professionals did not show higher positive attitudes towards vaccines. Furthermore, refusal percentage to vaccination was higher among healthcare professionals compared to non-healthcare professionals. Developing a strategy to increase positive attitudes against COVID-19 vaccine should be an objective for public health policy.